52‐3: Distinguished Paper: 3 Stacked Top Emitting White OLED for High Resolution OLED TV. Issue 1 (May 2016) - Jung, Young Kwan; Choi, Hong Seok; Ahn, So Yeon; Kim, Seunghyun; Choi, Heedong; Han, Chang Wook; Kim, Binn; Kim, Se June; Kim, Jongmoo; Choi, Jeong Hyeon; Yoon, SooYoung; Tak, Yoon Heung; et al.
Abstract : In this work, we report top emission white OLED (TE‐WOLED) device for an application to large sized and high resolution OLED TV. Like as bottom emission device, we adopted 3 stack WOLED consisting of two blue and one yellow green (YG) light‐emitting units with a reflective metal as the bottom anode and a transparent compound as the top cathode. By using an optical simulation, we designed the device structure and found optimum positions for EML with consideration of viewing angle property. As a result, we demonstrate top emission white OLED comparable to bottom emission OLED, regarding efficiency, operating voltage and viewing angle.